Do β-adrenoreceptor blocking drugs associate with reduced risk of symptomatic osteoarthritis and total joint replacement in the general population? A primary care-based, prospective cohort study using the Clinical Practice Research Datalink. Issue 8 (1st August 2019) - Nakafero, Georgina; Grainge, Matthew; Valdes, Ana; Townsend, Nick; Mallen, Christian; Zhang, Weiya; Doherty, Michael; Mamas, Mamas A; Abhishek, Abhishek
Abstract : Introduction: To investigate if β-adrenoreceptor blocking drug (β-blocker) prescription reduces the risk of knee or hip osteoarthritis, total joint replacement and analgesic prescription. Setting: Primary care. Methods and analysis: This is a cohort study using data from the Clinical Practice Research Datalink. Two separate analyses will be performed. Study 1 will be on the association between β-blocker prescription and incident knee/hip osteoarthritis. Inclusion criteria will be age ≥40 years. Exposed participants will be those with ≥2 continuous β-blocker prescriptions, and the index date will be the date of the first prescription of β-blocker. Unexposed participants will include up to four controls matched for age, sex, general practice surgery and propensity score for β-blocker prescription. Exclusion criteria will include contraindications to β-blockers, consultations for osteoarthritis or potent analgesic prescription before the index date. Outcomes will be knee osteoarthritis (primary outcome), hip osteoarthritis, knee pain and hip pain. Study 2 will be on the association between β-blocker prescription and total joint replacement and analgesic prescription in people with osteoarthritis. Inclusion criteria will be age ≥40 years, knee or hip osteoarthritis, and index date will be as in study 1. Unexposed participants will be as in study 1, additionally matched for consultation for knee or hip osteoarthritis prior to the index date. Exclusion criteria will include contraindications to β-blockers and osteoarthritis in other joints prior to the index date. Outcomes will be total knee replacement (primary outcome), total hip replacement and new analgesic prescription. Statistical analysis: Kaplan-Meier curves will be plotted, and Cox proportional HRs and 95% CIs will be calculated. Stratified analysis will be performed by class of β-blocker, intrinsic sympathomimetic effect and indication(s) for prescription. Ethics and dissemination: This study was ethically approved by the Independent Scientific Advisory Committee of the Medicines and Healthcare Authority (Ref 18_227R). The results of this study will be published in peer-reviewed journals and presented at conferences. Summary: This prospective cohort study will evaluate the analgesic potential of commonly used drugs for osteoarthritis pain.